Principles of dynamics of children's language picture of the world - E. V. Tarasenko (Гуманитарные и юридические исследования)
Introduction. In line with the anthropocentric approach, the desire to create a model of an individual linguistic worldview becomes possible thanks to concepts as basic structures for accumulating knowledge about the world. Such a result can be achieved by studying the children's language picture of the world, which will explain the structure of the language picture of the adult world, and not vice versa, as it seemed before.Materials and Methods. The research is based on the analysis of texts of a junior schoolboy using methods of observation, comparison, generalization of analysis and synthesis, interpretation of the data obtained empirically.Analysis. The works of Russian researchers describe fragments of the linguistic picture of the world of people of different professions who speak different languages. This article presents the author's point of view on the model of a fragment of the children's language picture of the world of a junior schoolboy. Predicates denoting mental activity as one of the numerous and leading groups of verbs in speech at this age are taken as a nuclear sphere of analysis. The principles of the dynamics of the image of the world, reflected in the language of the child, are revealed. The ontological principle is that the assimilation of the native language occurs through the assimilation of various models of structural schemes of sentences and their variants. The cognitive principle – proposition is a special stacked structure of knowledge storage, which is implemented and fixed by the structural scheme of the sentence. The communicative principle – speech acts expressed by the structural scheme of the sentence, implement the intentions of a native speaker. Thus, the structural schemes of sentences are the signifiers of syntactic concepts, and intentions and propositions are their signified. In a word, the syntactically represented concept controls the content of the sentence's structural scheme and the type of speech act, highlighting its individual cognitive features.Results. We have studied the connections of the cognitive basis of the concept with semantics and pragmatics, cause-and-effect relationships of actualization of ideas about mental activity by a younger student. Thus, the principles of the dynamics of the linguistic picture of the world form an initial position of objective reality conceptualization.